EFFICACY OF THE TRIS AND BIOCIPHOS PLUS EXTENDERS ON THE FREEZABILITY OF PUNGANUR BULL SEMEN - VEERABRAMHAIAH, K; RAO, A SESHAGIRI; RAO, V H; NAIDU, K VENUGOPAL; RAO, S T VIROJI (The Indian Journal of Animal Reproduction, 2023)
The present investigation was carried out to study the freezability of Punganur bull semen with Tris and Biociphos plus extenders. The difference in the individual sperm motility and live sperms between fresh and Biociphos plus extended semen and between Tris and Biociphos plus extended semen during pre-freeze and post-thaw periods was significant. The difference in head, mid- piece, tail and total sperm abnormalities between fresh and Tris extended semen was not significantly different but between Tris and Biociphos plus extended semen during pre-freeze and post-thaw periods was significant. Both the extenders were relatively non-toxic to sperm, but based on the sperm motility, livability, sperm abnormalities and acrosome damage Tris extender was concluded a better choice for preservation of Punganur bull semen.